2017
DOI: 10.1371/journal.pone.0181423
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of CHCA solvent compositions for improving LC-MALDI performance and its application to study the impact of aflatoxin B1 on the liver proteome of diabetes mellitus type 1 mice

Abstract: In nanoflow liquid chromatography-matrix-assisted laser desorption/ionization tandem time-of-flight (nanoLC-MALDI-TOF/TOF) approaches, it is critical to directly apply small amounts of the sample elutes on the sample target using a nanoLC system due to its low flow rate of 200 ~ 300 nl/min. It is recommended to apply a sheath liquid containing a matrix with a several μL/min flow rate at the end of the nanoLC column to ensure a larger co-eluted droplet for more reproducible sample spotting and avoid the laborio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…To investigate the effects of long-term exposure to AFB1 on type 1 diabetes mellitus (T1DM), some authors analysed the mice livers with T1DM after AFB1 treatment and highlighted that in the T1DM/AFB1 group the levels of the major urinary protein 1 (MUP1) were lower. Hence, considering that MUP1 is used as marker of higher insulin sensitivity, it is clear that AFB1 exposure induces the increased levels of blood glucose in mice and, also, the high probability to develop liver cancer [ 47 ]. Moreover, other studies demonstrated the importance of time intervals between AFB1 exposure and HCC development in absence and in presence of cirrhosis and HBV and evidenced that AFB1 exposure may increase in a dose-response manner the risk to develop cirrhosis and HCC in HBV patients [ 48 ].…”
Section: Aflatoxins Related Diseasesmentioning
confidence: 99%
“…To investigate the effects of long-term exposure to AFB1 on type 1 diabetes mellitus (T1DM), some authors analysed the mice livers with T1DM after AFB1 treatment and highlighted that in the T1DM/AFB1 group the levels of the major urinary protein 1 (MUP1) were lower. Hence, considering that MUP1 is used as marker of higher insulin sensitivity, it is clear that AFB1 exposure induces the increased levels of blood glucose in mice and, also, the high probability to develop liver cancer [ 47 ]. Moreover, other studies demonstrated the importance of time intervals between AFB1 exposure and HCC development in absence and in presence of cirrhosis and HBV and evidenced that AFB1 exposure may increase in a dose-response manner the risk to develop cirrhosis and HCC in HBV patients [ 48 ].…”
Section: Aflatoxins Related Diseasesmentioning
confidence: 99%
“…9 Moreover, AFB1 exposure in type 1 diabetic mice disrupted lipid, and oxidative phosphorylation, gluconeogenesis, and reduced major urinary protein 1 (a major insulin sensitivity indicator), with subsequent elevation of blood glucose level. 10 Therefore, the discovery of a new natural intervention becomes crucial. 11 A diet that contains high dietary fiber (DF) can improve the control of DM.…”
Section: Impact Statementmentioning
confidence: 99%
“…Although the liver plays vital roles in carbohydrate metabolism and regulation of blood glucose level, it is the target organ for AFB 1 [9]. Intoxication of T1DM mice with AFB 1 -disordered T1DM elevated energy-producing mechanisms, gluconeogenesis, lipid, and oxidative phosphorylation, reduced major urinary protein 1, insulin sensitivity indicator, and subsequently elevated blood glucose level [10]. There is a positive interaction between AFB 1 and diabetes in human subjects [11].…”
Section: Introductionmentioning
confidence: 99%